THEORETICAL FOUNDATIONS OF ARTISTIC THINKING AND VISUAL PERCEPTION IN VISUAL ARTS (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article investigates the theoretical foundations of artistic thinking and visual perception within the domain of visual arts, emphasizing their inseparable cognitive and aesthetic relationship. Artistic thinking is approached not as an auxiliary intellectual process or an innate creative ability, but as a historically and culturally conditioned mode of cognition that emerges through structured visual perception. From an authorial perspective, visual perception in art is conceptualized as an active, meaning-generating process in which sensory experience is transformed into aesthetic judgment, symbolic interpretation, and reflective awareness. The study critically engages with classical and contemporary theories of perception, aesthetics, and artistic cognition, revealing the limitations of approaches that isolate perception from thinking or reduce artistic understanding to technical skill acquisition. Through a theoretical-analytical methodology, the article demonstrates that artistic thinking develops within the internal logic of visual perception, where seeing functions as a form of intellectual activity rather than passive observation. The findings argue that visual arts constitute a unique epistemological field in which perception and thinking operate as a unified process, shaping artistic consciousness and aesthetic experience. The article concludes that a systematic theoretical understanding of this unity is essential for advancing art theory, art education, and the broader study of visual culture.